Sedation levels in dogs: a validation study - Marika C. Wagner; Kent G. Hecker; Daniel S. J. Pang (BMC Veterinary Research, 2017)
Abstract Background The aim of this study was to assess validation evidence for a sedation scale for dogs. We hypothesized that the chosen sedation scale would be unreliable when used by different raters and show poor discrimination between sedation protocols. A sedation scale (range 0–21) was used to score 62 dogs scheduled to receive sedation at two veterinary clinics in a prospective trial. Scores recorded by a single observer were used to assess internal consistency and construct validity of the scores. To assess inter-rater reliability, video-recordings of sedation assessment were randomized and blinded for viewing by 5 raters untrained in the scale. Videos were also edited to allow assessment of inter-rater reliability of an abbreviated scale (range 0–12) by 5 different raters. Results Both sedation scales exhibited excellent internal consistency and very good inter-rater reliability (full scale, intraclass correlation coefficient [ICCsingle] = 0.95; abbreviated scale, ICCsingle = 0.94). The full scale discriminated between the most common protocols: dexmedetomidine-hydromorphone (median [range] of sedation score, 11 [1–18], n = 20) and acepromazine-hydromorphone (5 [0–15], n = 36, p = 0.02). Conclusions The hypothesis was rejected. Full and abbreviated scales showed excellent internal consistency and very good reliability between multiple untrained raters. The full scale differentiated between levels of sedation.